2012
DOI: 10.1007/s10157-012-0673-8
|View full text |Cite
|
Sign up to set email alerts
|

Renal disease in the elderly and the very elderly Japanese: analysis of the Japan Renal Biopsy Registry (J-RBR)

Abstract: Renal biopsy is a valuable diagnostic tool, even in elderly and very elderly Japanese patients. In the future, modified clinical guidelines for elderly renal disease should be developed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
0
8

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 21 publications
5
54
0
8
Order By: Relevance
“…The incidence of hypertension in the older group was significantly higher than in the younger group. In the incidence data, proteinuria was significantly different between the groups [13,24]. Moreover, other studies also found proteinuria was significantly different between the groups [18,20,21].…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The incidence of hypertension in the older group was significantly higher than in the younger group. In the incidence data, proteinuria was significantly different between the groups [13,24]. Moreover, other studies also found proteinuria was significantly different between the groups [18,20,21].…”
Section: Resultsmentioning
confidence: 88%
“…Three studies found baseline renal function of the older groups was generally worse than that of the younger groups [13,21,24], but the time between disease onset and diagnosis in the older group and the younger group was not significantly different, which proves that aging itself can damage renal function in IgAN patients and adversely impact IgAN prognosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the Japan Renal Biopsy Registry [2], MCNS accounts for 13.8 % of nephrotic syndrome cases in the elderly ([65 years). There has been an increasing incidence of patients with a variety of complications at the time of nephrotic syndrome onset, especially in the elderly.…”
Section: Introductionmentioning
confidence: 99%